EVALUASI PROSEDUR PEMUNGUTAN CUKAI MINUMAN BERALKOHOL BUATAN DALAM NEGERI PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C KENDARI - Kapantouw, Jenni Febriyanti; Elim, Inggriani; Mawikere, Lidia (Universitas Sam Ratulangi, 2016)
Excise levies is one component of state revenues that have specific characteristics and different from other tax levies, one type of goods subject to excise that need to be monitored and controlled production and circulation ie excise beverages containing ethyl alcohol, or also known as non-alcoholic beverages. The purpose of this study is to evaluate the tax collection procedure alcoholic beverages domestically. This type of research is qualitative descriptive study to give a clear picture of the issues examined. The results obtained that the procedures for collecting excise alcoholic beverages domestically in KPPBC TMP C Kendari indeed in accordance with Law No. 39 of 2007 concerning amendments to the Law No. 11 Year 1995 on Customs, but there are some provisions excise alcoholic beverages artificial in the country that need to be refined in the regulations by the Director General of Customs and Excise KPPBC TMP C Kendari. TMP C Kendari KPPBC should more thoroughly in the collection of the alcoholic beverage excise, so hope that KPPBC Kendari TMP C is more active in activities such as dissemination to entrepreneurs factory.Keywords: Evaluation Procedures, Collection of Customs